Agronomic use efficiency of N fertilizer in maize-based systems in sub-Saharan Africa within the context of integrated soil fertility management - Vanlauwe, Bernard; Kihara, Job Maguta; Chivenge, Pauline P.; Pypers, Pieter; Coe, R.; Six, Johan (Springer, 2011)
Traditionally, crop production in sub-Saharan Africa (SSA) depends primarily on mining soil nutrients. Integrated Soil Fertility Management (ISFM) is an approach for intensifying agriculture in SSA that aims at maximizing the agronomic efficiency (AE) of applied nutrient inputs. ISFM contains the following essential components: proper fertilizer management, use of improved varieties, the combined application of organic inputs and fertilizer, and adaptation of input application rates to within-farm soil fertility gradients where these are important. This paper evaluates, through meta-analysis, the impact of these components on the AE of fertilizer N (N-AE), defined as extra grain yield per kg fertilizer N applied, in maize-based systems in SSA. Since N-AE is low for excessive fertilizer N application rates or when fertilizer is applied on fertile, unresponsive soil, as was confirmed by scatter plots against control yields and fertilizer N application rates, such values were removed from the database in order to focus on and elucidate the more variable and complex responses under less than ideal conditions typical for SSA. Compared with local varieties, the use of hybrid maize varieties significantly increased N-AE values (17 and 26 kg (kg N)?1, respectively) with no differences observed between local and improved, open-pollinated varieties. Mixing fertilizer with manure or compost resulted in the highest N-AE values [36 kg (kg N)?1] while organic inputs of medium quality also showed significantly higher N-AE values compared with the sole fertilizer treatment but only at low organic input application rates (40 and 23 kg (kg N)?1, respectively). High quality organic inputs (Class I) and those with a high C-to-N ratio (Class III) or high lignin content (Class IV) did not affect N-AE values in comparison with the sole fertilizer treatment. Application of N fertilizer on infields resulted in significantly higher N-AE values [31 kg (kg N)?1] compared with the outfields [17 kg (kg N)?1]. The obtained information indicates that N-AE is amenable to improved management practices and that the various components embedded in the ISFM definition result in improvements in N-AE.